Evaluation of Composite Cephalometric Norms in South Indian Subjects (Orthodontic Journal of Nepal, 2015)
Introduction: Cephalometrics is an important diagnostic tool in formulating comprehensive treatment planning in orthodontics. Different norms for different ethnic groups are essential to achieve accurate treatment results.Objective: The present study aims in standardizing norms for composite cephalometric analysis in South Indian subjects.Materials & Method: A sample size of 40 subjects included 20 males and 20 females of age ranging between 18-30 years represented South Indian sample. Patients’ cephalogram was taken in the natural head position. Individual norms from various cephalometric analyses were taken and synthesized into a composite analysis based on the idea of diagnostic block were evaluated.Results: Parameters like upper incisor to NA, lower incisor to NB, interincisal angle, IMPA and upper incisor to SN suggested increased values indicating proclination of anterior teeth and mild convexity of soft tissues to be esthetically acceptable in South Indian subjects.Conclusion: Different set of cephalometric norms for different ethnic groups should be formulated so as to guide the orthodontist and surgeon to optimize the treatment plan based on local norms